Molecular epidemiology of Klebsiella pneumoniae isolates causing invasive disease from a private laboratory in South Africa - Kock, Marleen (University of Pretoria, 2024)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2024.